Optimization of laser cutting quality characteristics for basalt –glass hybrid composite using hybrid approach. (2022) - Jain, Akshay; Agarwal, Anupma; Chauhan, Premanand S
Abstract: In this research work, hybrid composite with combination of basalt fiber and glass fiber have been fabricated by the hand lay composite manufacturing technique. Moreover, its mechanical testing have been conducted. It has been perceived that fabricated hybrid composite has superior mechanical testing results. Precise machining of these composites is a tedious task. There are various limitations in conventional machining such as: fiber pullout, delamination, burr formation, crack formation in matrix etc., which can cause for poor machined surface and it also reduce mechanical performance of the hybrid composite. Laser machining can be one of the best alternative because of its non-contact nature with high production rate. In the present study, Artificial Neural Network (ANN) merged with genetic algorithm (GA) hybrid technique has been used to investigate the effects of machining parameters on responses.